2016
DOI: 10.1016/j.jcrc.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early do-not-attempt-resuscitation orders on procedures and outcomes of severe sepsis

Abstract: Purpose Do-not-attempt-resuscitation (DNAR) orders are common in severe sepsis, but the impact on clinical care is not known. Our primary objective was to determine the impact of early DNAR orders on in-hospital mortality and performance of key interventional procedures among severe sepsis hospitalizations. Our secondary objective was to further investigate what patient characteristics within the sepsis DNAR population affected outcomes. Methods Using the 2010–2011 California State Inpatient Dataset, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…[29,30] Interestingly, in our study, rates of DNR orders within 24 hours -which varied nearly tenfold between hospitals -were not associated with survival or good neurologic recovery at hospital discharge. The variation we found aligns with prior studies showing variation between hospitals in DNR ordering practices, [31][32][33] but our lack of association with outcomes contrasts with prior studies focused on in-hospital cardiac arrest, [32,33] severe sepsis, [34] and severe traumatic brain injury. [31] Lack of association with outcomes may indicate that physicians are appropriately using early DNR orders in patients with underlying terminal illnesses or clearly non-survivable conditions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[29,30] Interestingly, in our study, rates of DNR orders within 24 hours -which varied nearly tenfold between hospitals -were not associated with survival or good neurologic recovery at hospital discharge. The variation we found aligns with prior studies showing variation between hospitals in DNR ordering practices, [31][32][33] but our lack of association with outcomes contrasts with prior studies focused on in-hospital cardiac arrest, [32,33] severe sepsis, [34] and severe traumatic brain injury. [31] Lack of association with outcomes may indicate that physicians are appropriately using early DNR orders in patients with underlying terminal illnesses or clearly non-survivable conditions.…”
Section: Discussionsupporting
confidence: 81%
“…[7] It may also indicate that physicians are appropriately interpreting DNR orders as a directive to not initiate cardiopulmonary resuscitation in the event of a recurrent cardiac arrest and not a directive to withhold other treatments or interventions, in contrast to prior studies. [32][33][34] The observed variation in cardiac catheterization and early DNR orders may represent differential uptake of evidence-based practices at 24/7 PCI centres. DNR orders within 24 hours may represent early prognostication and DNR order discussions with families, in contrast to current guidelines which recommend deferring prognostication until 72 hours for most patients resuscitated from OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…An independent association between DNR orders and mortality has previously been demonstrated in other areas of medicine, including patients with septic shock and patients with acute surgical disorders [1,2,23]. This leaves the question whether patients with a DNR order died because they received less aggressive and/or inferior treatment or that a DNR order rather mirrors the natural history of CAP in fragile patients.…”
Section: Discussionmentioning
confidence: 97%
“…This leaves the question whether patients with a DNR order died because they received less aggressive and/or inferior treatment or that a DNR order rather mirrors the natural history of CAP in fragile patients. In septic patients with DNR orders, Sakari et al [ 2 ] recorded fewer invasive procedures indicating less aggressive treatment. Further, previous studies investigating physicians’ interpretation of DNR orders have shown that they are misinterpreted to mean that essential steps of treatment such as contacting a doctor upon deterioration, fluid resuscitation and other supportive treatment, may be omitted [ 24 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation